MANAJEMEN PEMBIAYAAN PENDIDIKAN DI SDN KAWUNGSARI GIRANG KECAMATAN BALEENDAH KABUPATEN BANDUNG - Ujang Cepi Barlian; Euis Sumiati; Raden Yulyul Yuliana Hastuti (Bajang Institute, 2022)
Challenges and obstacles faced by the world of education ranging from technology and scientific progress. In general, this study aims to describe the effectiveness of the management of School Operational Assistance (BOS) funds for education financing at SDN Kawungsarigirang Kec. Baleendah Kab. Bandung. This study uses a qualitative method with a descriptive approach. Then, the observations were located at SDN Kawungsarigirang, Cikawung Village, Wargamekar Village, Baleendah District, Bandung Regency. The researcher concludes that education financing management is a series of activities that regulate school finances starting from planning, bookkeeping, spending, supervision and accountability of school finances with control over management functions to realize the achievement of organizational goals. Educational financing management includes a series of activities consisting of school financing planning, implementation, and control of school financing.